Burnout among Portuguese Sign Language Interpreters following the third pandemic wave of COVID-19: A cross-sectional mixed methods study - Barbosa, Susana; Alves, Sílvia; Branco, Susana; Oliveira, Ana; Serrão, Carla (Sensos-e, 2025)
During the COVID-19 pandemic, Portuguese sign language interpreters (SLIs) had to adapt quickly to the new context. One of the biggest challenges was developing their activity online. This study, grounded in the theoretical frameworks of burnout (Maslach & Leiter, 2016) and perceived stress (Lazarus & Folkman, 1984), aimed to identify the factors influencing SLIs’ vulnerability to burnout and to explore their perceptions of the impact of the COVID-19 outbreak, as well as potential mitigation strategies. A cross-sectional, quantitative and qualitative online study examined burnout, stress perception, satisfaction with life and COVID-19 impact. A total of 110 SLIs completed the questionnaire. Personal (59%), work‐ (46%) and patient‐related (24%) burnout was observed. Three significant models explained personal‐ (R2 = 54%), work‐ (R2 = 46%) and client‐related burnout (R2 = 22%). The results showed that only perceived stress levels significantly predict personal, work- and client-related burnout in SLIs. From the participants' perspective, the COVID-19 context triggered difficulties in the excessive working hours, work-life imbalance, reduced energy and quality of life, and lack of resources and digital literacy. As suggestions to minimize this impact, the SLI indicate the need to re-think educational adjustments during emergency remote learning, provide SLIs with psychological and tangible support and reinforce communication mechanisms among educational members.